2017
DOI: 10.1103/physrevb.96.024504
|View full text |Cite
|
Sign up to set email alerts
|

Fast microwave-driven three-qubit gates for cavity-coupled superconducting qubits

Abstract: Although single and two-qubit gates are sufficient for universal quantum computation, single-shot three-qubit gates greatly simplify quantum error correction schemes and algorithms. We design fast, high-fidelity three-qubit entangling gates based on microwave pulses for transmon qubits coupled through a superconducting resonator. We show that when interqubit frequency differences are comparable to single-qubit anharmonicities, errors occur primarily through a single unwanted transition. This feature enables th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…Accordingly, we adopt a baseline superconducting noise model, labeled as SC, corresponding to a superconducting device which has 10x lower gate errors and 10x longer T 1 duration than the current IBM hardware. This range of parameters has already been achieved experimentally in superconducting devices for gate errors [55,56] and for T 1 duration [57,58] independently. Faster gates Noise Model 3p 1 15p 2 T 1 SC 10 −4 10 −3 1 ms SC+T1 10 −4 10 −3 10 ms SC+GATES 10 −5 10 −4 1 ms SC+T1+GATES 10 −5 10 −4 10 ms Table 2: Noise models simulated for superconducting devices.…”
Section: Superconducting Qcmentioning
confidence: 52%
“…Accordingly, we adopt a baseline superconducting noise model, labeled as SC, corresponding to a superconducting device which has 10x lower gate errors and 10x longer T 1 duration than the current IBM hardware. This range of parameters has already been achieved experimentally in superconducting devices for gate errors [55,56] and for T 1 duration [57,58] independently. Faster gates Noise Model 3p 1 15p 2 T 1 SC 10 −4 10 −3 1 ms SC+T1 10 −4 10 −3 10 ms SC+GATES 10 −5 10 −4 1 ms SC+T1+GATES 10 −5 10 −4 10 ms Table 2: Noise models simulated for superconducting devices.…”
Section: Superconducting Qcmentioning
confidence: 52%
“…The authors conjecture that this is the case for gates within a small neighborhood of any given fast gates, i.e., gates which can be implemented by the controls alone. Furthermore, recently it has been shown that simple analytically obtained pulses can lead to high fidelity gates  » 0.01 [67,68]. Further numerical control optimization yields yet higher fidelities at the cost of requiring significantly higher frequency components within the numerically optimized pulse [68].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recently it has been shown that simple analytically obtained pulses can lead to high fidelity gates  » 0.01 [67,68]. Further numerical control optimization yields yet higher fidelities at the cost of requiring significantly higher frequency components within the numerically optimized pulse [68]. It would be favorable to obtain criteria characterizing the set of gates for which 'simple' pulses exist and further to understand the highest frequency required in a pulse to implement a gate perfectly.…”
Section: Discussionmentioning
confidence: 99%
“…In the dispersive regime, the simplest way to ensure that this transition is the only one excited by the pulse is to use a very narrowband pulse-an approach which necessarily leads to long gate times. To avoid making this sacrifice in gate speed, we instead employ the SWIPHT method 43,46 to remove the effects of inadvertently driving unwanted transitions without resorting to spectrally narrow, slow pulses. For typical experimental values of the qubit-cavity couplings g 1,2 , there is exactly one nearest "harmful" transition, namely the |001 ⇔ |011 transition, which competes with the target transition, |000 ⇔ |010 .…”
Section: 45mentioning
confidence: 99%